Al2O3-Water Nanofluid Jet Impingement Cooling With Magnetic Field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2020)
Numerical study of double jet impingement cooling of an isothermal surface with Al2O3-water nanofluid under the influence of magnetic field was performed. Galerkin-weighted residual finite element method was utilized for the solution of the governing equations. The numerical simulations were performed for various values of Reynolds number (between 100 and 400), solid particle volume fraction (between 0 and 4%), and Hartmann number (between 0 and 2.5). The ratio of the slot-to-plate distance was varied between 4 and 16 whereas ratio of the distance between the slots to slot width was varied between 5 and 22.5. It was observed that magnetic field retarded the fluid flow and reduced the local and average heat transfer. At the highest value of the Hartmann number, the fluid cannot reach the stagnation point. Depending on the distance between the slots and slots to plate distance, average heat transfer enhances by about 46% and its value increases linearly with nanoparticle volume fraction. This study is particularly important where magnetic field is present and weakens the convective heat transfer characteristics in jet impingement cooling whereas it is possible to enhance its thermal performance by utilization of nanoparticles.
Keywords: Heat-Transfer Enhancement; Natural-Convection; Forced-Convection; Mixed Convection; Turbulent Jet; Slot Jets; Flow; Channel; Cavity; Fluid